Clinical Manifestation of Peripheral Artery Disease in Type 2 Diabetes Melitus with Ankle Branchial Index Measurement - Winny W Nasution; Henhen Heryaman; Januar W Martha; Apen A Ridwan (Universitas Kristen Maranatha, 2019)
Diabetes mellitus (DM) is a metabolic disease that has a high prevalence in Asia, including Indonesia. One of the complications of DM is Peripheral Artery Disease (PAP). Ankle Brachial Index (ABI) measurement is a simple and non-invasive methods that can be used for PAP evaluation. This study aims to provide an overview of the clinical manifestations of PAP and the value of ABI as early detection of PAP in patients with type-2 DM. This research uses quantitative descriptive design studies. The research variables used to assess PAP were ABI values, age, sex, duration of diabetes mellitus, hypertension, and clinical manifestations of PAP such as pain, intermittent claudication, muscle atrophy, skin discoloration, sweating, wound healing impairment, and gangrene. This study involved 92 research subjects. From the study we found out that the normal ABI value and the ABI value of the PAP category in patients with type 2 diabetes were 91.3% and 7.6%. The ABI value of the PAP category in DM patients is more commonly found in women (6.5%), adult patients (5.4%), duration of DM up to 2 years (5.4%), and with hypertension (5.4%) . Pain and numbness are the most common clinical manifestations of PAP in DM patients. Keywords: diabetes mellitus, ankle brachial index, peripheral artery disease.